Shallow foundations : bearing capacity and settlement - Das, Braja M., 1941- (CRC Press, 2009)
Considered the standard engineering reference on shallow foundations, this edition strengthens that position. Completely reworked and written by one of the top men in the field, it covers all the latest developments and approaches. Equally valuable to researchers and designers as it is to engineering students, this resource updates data and provides revised theories on the ultimate and allowable bearing capacities of shallow foundations. It adds refinements to a number of unique circumstances such as foundations on soil with geogrid reinforcement as well as bearing capacity relationships for s.